STYLISTIC DEVICES AS A VERBALIZERS OF THE CATEGORY OF INTENSIFICATION/DEINTEN-SIFICATION IN THE LANGUAGE - Ziyaev Avazjon; Abdunazarova Nilufar Yorqin Qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article touches upon expression of intensification with the help of stylistic devices, which allowed the author to reveal the universal features of the verbalizers and the factors preconditioning the latter. The role of stylistic devices in expressing intensification is extremely large. With the help of stylistic devices, the speaker has the opportunity to clearly, exaggerate and intensify his opinion to the listener. Almost all stylistic devices in the English language system participate in the process of expressing intensification. In this article the author tried to analyze only some of them.